PERLINDUNGAN HUKUM PEMEGANG HAK ATAS TANAH BEKAS ERFPACHT DALAM HAL TERJADI TUMPANG TINDIH SERTIFIKAT (Studi Kasus Putusan Nomor 793K/Pdt/2022) - Ariq Fazari (Universitas Warmadewa, Denpasar, Bali, 2023)
The implementation of the UUPA resulted in land with a western legal status or customary law being converted according to the UUPA provisions, but there were still case of conversion land disputes in which there were overlapping certificates. The purpose of this study was to determine the status of legal status between certificates and business certificates on land used for erfpacht status as well as the legal protection of property owners, namely farmers in Tegalrejo village, on the issue of certificates of business use in the name of PTPN XII on land owned by farmers. The method in this is normative juridicial, i.e. through the review of legislation with the support of secondary materials. The problem approach to this study was the case approach by obtaining data through a library study and then the data that had been obtained was analyzed using a descriptive analysis method that was interpreted to obtain the answer to the problem. The results of the study were found that the certificate of property of farmers in Tegalrejo village was given on the land the distribution of former land of haberfpacht may be revoked under Article 18 of the UUPA for the benefit of the state, which in case is for the purpose of land use of PTPN XII with the issuance of a certificate of business use. Farmers in Tegalrejo Village can protect property rights on their land through submitting a lawsuit to the public court and/or TUN. In addition, farmers in Tegalrejo Village deserve compensation in proportion to their land that is revoked